High thermal stability of electric field-induced strain in (1−x)(Bi0.5Na0.5)TiO3-xBa0.85Ca0.15Ti0.9Zr0.1O3 lead-free ferroelectrics. Issue 2 (February 2019) - Jin, Li; Luo, Wenting; Wang, Liang; Tian, Ye; Hu, Qingyuan; Hou, Lei; Zhang, Lin; Lu, Xu; Du, Hongliang; Wei, Xiaoyong; Liu, Gang; Yan, Yan
Abstract: In ferroelectric materials high electric field-induced strain (EFIS) with good thermal stability is of much interest from both fundamental research and potential applications. Here we propose a strategy to achieve high thermally stable EFIS based on electrostrictive effect and thermal stability of polarization. According to this strategy, we synthesized (1− x )(Bi0.5 Na0.5 )TiO3 - x Ba0.85 Ca0.15 Ti0.9 Zr0.1 O3 (BNT- x BCZT) ferroelectric ceramics in order to tailor the thermal stability of dielectric permittivity, polarization and EFIS. A dielectric platform with a wide temperature region is induced by increasing x from 0.24 to 0.36 gradually. From 30 °C to 150 °C, a variation of 20% polarization results in a change of 36% EFIS, suggesting a good thermal stability as expect. Temperature-insensitive electrostrictive coefficient Q 33 ranges from 0.0264 m 4 /C 2 to 0.0314 m 4 /C 2 . These results not only prove the effectiveness of this strategy, but also suggest that this strategy can be applied to other ferroelectric materials to improve the thermal stability.